Using Precisely Defined in vivo Microbiotas to Understand Microbial Regulation of IgE - Wyss, Madeleine; Brown, Kirsty; Thomson, Carolyn A.; Koegler, Mia; Terra, Fernanda; Fan, Vina; Ronchi, Francesca; Bihan, Dominique; Lewis, Ian; Geuking, Markus B.; McCoy, Kathy D. (Frontiers in Immunology, 2020)
Early life exposure to microbes plays an important role in immune system development. Germ-free mice, or mice colonized with a low-diversity microbiota, exhibit high serum IgE levels. An increase in microbial richness, providing it occurs in a critical developmental window early in life, leads to inhibition of this hygiene-induced IgE. However, whether this inhibition is dependent solely on certain microbial species, or is an additive effect of microbial richness, remains to be determined. Here we report that mice colonized with a combination of bacterial species with specific characteristics is required to inhibit IgE levels. These defined characteristics include the presence in early life, acetate production and immunogenicity reflected by induction of IgA. Suppression of IgE did not correlate with production of the short chain fatty acids propionate and butyrate, or induction of peripherally induced Tregs in mucosal tissues. Thus, inhibition of IgE induction can be mediated by specific microbes and their associated metabolic pathways and immunogenic properties.